PEMANFAATAN MATERIAL BIODEGRADABLE (BESE-ELEMENT) SEBAGAI MEDIA RESTORASI MANGROVE DI PESISIR NEGERI PASSO, KOTA AMBON - Gino V. Limmon; Rahman Rahman; Frijona Fabiola Lokollo; Eelco Waardenburg; Wouter Lengkeek; Peter Vodegel (Bajang Institute, 2023)
Mangrove ecosystems have potential both ecologically, economically, physically, and chemically. The abundance of this potential causes pressure from anthropogenic activities, which results in the degradation of mangrove ecosystems. Several mangrove ecosystems in the Ambon City area have experienced degradation, so restoration is necessary. The Passo State area has the potential for a dense mangrove ecosystem and can be used as a nursery area to support other ecosystems. Increasing the potential of mangrove ecosystems in the Passo State area can be done through restoration using biodegradable materials (BESE-Elements). Mangrove restoration is carried out through community service activities, a collaboration between the Maritime Center and Wardeen Burg Ecology – The Netherlands. The result of the activity is that mangrove ecosystem restoration is carried out in semi-enclosed areas using 10 BESE-Element. Each BESE-Element was planted with 10 mangrove seedlings consisting of 5 seedlings and 5 propagules. The mangrove species planted were Bruguiera gymnorrhiza, Rhizophora apicutala, and Rhizophora stylosa. Around BESE-Elements planted seedlings and mangrove propagules as a control for mangroves in BESE-Elements.